A influência do mercado de trabalho na desigualdade de renda no Maranhão: um diagnóstico para o período de 2012 a 2020 - MUNIZ, Thiago Souza (2023)
Based on the fundamental concern about the dynamics of income inequality in Maranhão, the research problem is the search to understand whether female unemployment is associated with income inequality. Thus, based on the relationship between the labor market and income inequality, this dissertation has the main objective of investigating the influence of unemployment by gender caused by the labor market in Maranhão in explaining income inequality measured by the Gini Index of per capita household income. capita between 2012 and 2020. For this, data from the Quarterly Continuous PNAD are used. Among the results obtained, there was a significant association between the level of unemployment and underutilization of the workforce in relation to income inequality, as well as the importance of gender inequality in the labor market to explain income inequality in Maranhão, during the analyzed period.